Effect of Robusta Coffee Bean Extract as Immunoregulator on Dental Pulp Mesenchymal Stem Cells via Paracrine Pathway - Desi Sandra Sari; Millenieo Martinindo; Syafika Nuring Fadiyah; Indah Yulia Ningsih; Tantin Ermawati Tantin Ermawati; Zahara Meilawaty; Dessy Rachmawati; Ernie Maduratna; Fedik Abdul Rantam (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To analyze the  effect of Robusta Coffee Bean Extract (RCBE) on Dental Pulp Mesenchymal Stem Cells (DPSCs) culture in secreting cytokines, growth factors, and cell differentiation. Material and Methods: DPSCs culture from premolar human teeth only and DPSCs culture from premolar human teeth given RCBE with concentrations of 0.0625%, 0.125%, 0.25%, and 0.5% for 24 hours, 48 hours, and 72 hours. The secretome of the DPSCs culture was examined for TNF-α, IFN-g, IGF, and VEGF, examination of SOX2 and Oct4, and Wnt differentiation markers by ELISA. Statistical analysis used ANOVA and continued with LSD. Results: There was a significant reduction in the levels of TNF-α and IFN-g at 0.25% RCBE concentration at 72 hours of immersion (p<0.05). Growth factor levels of IGF and VEGF increased when given 0.25% RCBE compared to the other groups, and the differentiation markers SOX2 and Oct4 and Wnt also increased at a concentration of 0.25% at 72 hours of immersion (p<0.05). Conclusion: Giving RCBE with a concentration of 0.25% can reduce inflammatory cytokines and increase growth factors and differentiation markers in DPSCs cultures.